Digital Narrative: A Framing Analysis of the “Stop Judi Ya Guys” Campaign by Mobile Legends Influencers in the Boycott of Online Gambling - Gilang Adjie Prayudha; Nursapia Harahap (CV. AFDIFAL MAJU BERKAH, 2025)
This article examines the framing strategy in the digital campaign “Stop Judi Ya Guys” conducted by Mobile Legends influencers in response to the spread of online gambling in the digital space of young people. The urgency of this study lies in the massive normalization of online gambling in digital entertainment media and the weak digital literacy of the younger generation, which allows the infiltration of deviant values through gaming and live streaming platforms. This research employs a qualitative method with a virtual ethnographic approach to explore the construction of narratives and public responses to the campaign. Data collection techniques include observing digital content on YouTube, conducting in-depth interviews with influencers, their followers, and digital communication experts. Data analysis uses the Miles, Huberman, and Saldana model, which includes data reduction, data presentation, and verification. Data validity was tested through source triangulation and expert triangulation to ensure consistency between the campaign narrative and the digital actions that occurred. The results of the study indicate that the representation of online gambling occurs subtly through symbols, game features, and digital forums, forming a normalization process that is difficult to recognize. Conversely, the digital campaign by influencers uses an organic, contextual, and participatory approach to build a moral counter-narrative. The discussion emphasizes the importance of framing and innovation diffusion as social intervention strategies within digital communities. In conclusion, the strength of digital campaigns lies in integrating values into the daily digital lives of audiences through familiar, emotional, and participatory communication styles.